SAGC Circuit Design and Implementation for FSK Modem through Radio Channel - Apichat Sutam; Apiwat Magkeethum; Paramote Wardkein; Jeerasuda Koseeyaporn; Sukkharak Saechia (My University, 2021)
In this research, the sinusoidal automatic gain control circuit (SAGC) has been fabricated by using differentiator circuits, multiplier circuits, a summation circuit, a square root circuit and a division circuit. By using an Operational amplifier (Op amp) and 2 capacitors, the differentiator circuit has been constructed An Op amp and IC AD633 used as a multiplier are combined for fabricating the square root circuit [1]. Apart from evaluating the SAGC characteristics, the FSK recovery process for transmitting the (Global Positioning System) GPS coordinates through radio channel has been improved via the proposed SAGC circuit. The results show that the proposed circuits and its implementation operate perfectly and agree well with the conventional theory.
Keywords: Sensor Technology and Measurement Systems; Embedded Systems and FPGA Design; Magnetic Bearings and Levitation Dynamics